Remembering a name: Neuropsychological validity studies and a computer proposal for detection of anomia - Vigliecca, Nora Silvana (2019)
There are contradictory results or lack of validity studies concerning the naming function and brain laterality. Although anomia is a frequent symptom of memory impairment, and the most relevant symptom of aphasia, few studies have been conducted to evaluate its validity for detecting patients with left hemisphere damage (LD) as per the MeSH definition. Objectives: To validate a paper-and-pencil confrontation naming test (CNT) according to side of brain injury. To select a valid and reliable abbreviated CNT wherein the effect of demographic variables is minimized. To use the selected CNT to develop a computer-aided confrontation-naming evaluation (CACNE). Methods: Control data were obtained from 213 healthy participants (HP) aged 15 to 89. A subsample of 106 HP was demographically matched to 39 LD and 40 patients with right hemisphere damage (RD). Anomia definition and CNT cues were considered for CACNE. Results: Test-retest and inter-rater reliability, internal consistency, and validity for detecting LD were demonstrated. A significant age effect was observed in HP. CACNE was developed to detect anomia in interaction with environmental interventions. Conclusion: The inconsistencies observed in CNT studies, were probably due to the presence of anomia in almost 50% of RD.